Pengaruh Green Produk, Label Halal dan Harga Terhadap Keputusan Pembelian Produk UMKM Rempeyek Ilhamumtaza Kota Jambi - Ading Nadia Sansabilla; Rafidah Rafidah; Mohammad Orinaldi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This thesis aims to find out the influence of green products, halal labels and prices on purchasing decisions for Umkm Rempeyek Ilhamumtaza products in Jambi City. The research here uses quantitative research methods. The approach used in this research is the descriptive-quantitative method. The research results show (1) a Sig value of 0.000 < 0.005. This means that Green Products have a significant effect on purchasing decisions. And it can be seen that the t-count value is 5.878 > 1.985 from the t-table. This means that Green Products influence purchasing decisions or the first hypothesis is accepted. (2) the Sig value is 0.001 < 0.005. This means that the halal label has a significant effect on purchasing decisions. And it can be seen that the t-count value is 3.562 > 1.985 from the t-table. This means that the halal label has an influence on purchasing decisions or the second hypothesis is accepted. (3) Sig value is 0.000 < 0.005. This means that price has a significant influence on purchasing decisions. And it can be seen that the t-count value is 8.461 > 1.985 from the t-table. This means that price influences purchasing decisions or the third hypothesis is accepted. (4) the Sig value is 0.000 < 0.05, this means that Green Product, Halal Label and Price together (simultaneously) have a significant influence on purchasing decisions or the fourth hypothesis is accepted.